Effects of Inulin Consumption on the Gut Microbiome During Fasting: A Pilot Study in Healthy Volunteers. (7th June 2021) - Thriene, Kerstin; Amend, Lena; Strowig, Till; Michels, Karin
Abstract: Objectives: Caloric restriction has been associated with beneficial effects on metabolic diseases such as type 2 diabetes, cardiovascular diseases, and cancer but the mechanisms are diverse and not fully understood. Interactions between the human host and its gut microbiota might play a crucial role in this context, but these have not yet been analysed in detail. Therefore, we conducted a pilot intervention study to investigate how the microbial community in the human gut adapts to caloric restriction. Additionally, we investigated whether the compliance improved if the participants during fasting consumed prebiotics, which are supposed to reduce sensations of hunger while not providing calories through digestion in the small intestine. Methods: We recruited six healthy volunteers (age: 20–50 years, BMI: 20–25 kg/m 2 ) for a pilot intervention study using a randomized crossover design. The study consisted of two sequential fasting periods of which one included additional prebiotics. Participants were fasting for three consecutive days consuming a total of 300 kcal daily provided by vegetable juices, framed by two days with a total daily calorie intake of 800 kcal, respectively. During one of the fasting periods, participants consumed additionally 24 g of inulin daily. Stool samples were collected for the analysis of the microbial composition by 16S rRNA sequencing. Results: We observed no clear change in alpha diversity during the period of caloric reduction. However, quantitative changes in the composition of the microbiome was visible in mainly all participants. Additional intake of the prebiotic inulin did not influence compliance for the fasting intervention. However, we observed a clear reduction in alpha diversity in the gut microbiome after inulin ingestion during the fasting period. Conclusions: Caloric restriction appears to have no significant influence on the gut microbiome itself but inulin consumption during fasting seems to selectively promote the growth of some bacterial families leading to an overall decrease of alpha diversity in the gut microbiome. Further studies with a larger sample size are warranted to verify our observations. Funding Sources: Institutional budget, no external funding.